Rozwój controllingu na obszarze europejskim - Janczyk-Strzała, Elżbieta (Growing Trends of Controlling in Europe, 2005)
This article is dedicated to the significant role of controlling in European countries. It describes its growing trends in Europe.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 35-39